presenting a model for controlling and monitoring urban constructions from the perspective of urban management ( case study of Tehran municipality region 13 ) (Scientific Journal of Research Studies in Future Management, 2023)
urban construction problems and related violations in the mass age of the population is one of the challenges that disregard them structural , superficial and functional damages to cities and related cases . accordingly , supervision and management are very important on the basis of the existing model in this field . in this regard , this study was designed to provide a model for controlling and monitoring urban constructions from the perspective of urban management . this descriptive research was exploratory and the population consisted of all experts , experts and managers and experts of the construction section of the city that 385 of them completed the questionnaire that confirmed its psychometric properties . among 31 indicators , 5 main factors can be identified . these factors were named according to experts opinion and based on content analysis concepts of construction rules and regulations , multi - axial regulatory commissions , urban planning , operational - operational management and operation speed in dealing with violation and construction deviations and these five factors explained 73 percent of the variance of the variables in the variables .